2017
DOI: 10.1002/2016jd026398
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down estimate of methane emissions in California using a mesoscale inverse modeling technique: The San Joaquin Valley

Abstract: We quantify methane (CH4) emissions in California's San Joaquin Valley (SJV) by using 4 days of aircraft measurements from a field campaign during May–June 2010 together with a Bayesian inversion method and a mass balance approach. For the inversion estimates, we use the FLEXible PARTicle dispersion model (FLEXPART) to establish the source‐receptor relationship between sampled atmospheric concentrations and surface fluxes. Our prior CH4 emission estimates are from the California Greenhouse Gas Emissions Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 34 publications
(103 reference statements)
9
50
1
Order By: Relevance
“…Similarly, long-term measurements by Jeong et al (2016) estimated that CH 4 emissions from dairy livestock in the San Joaquin Valley are 2 times greater than the California Air Resource Board (CARB) estimates. Short-term measurements by Trousdell et al (2016) and Cui et al (2017) estimated that CH 4 emissions from dairy livestock in the San Joaquin Valley are up to 2.4 times greater than CARB estimates. Other regional short-term TD measurements have suggested that dairy livestock emissions are similar to CARB estimates (Peischl et al, 2013;Wecht et al, 2014b).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, long-term measurements by Jeong et al (2016) estimated that CH 4 emissions from dairy livestock in the San Joaquin Valley are 2 times greater than the California Air Resource Board (CARB) estimates. Short-term measurements by Trousdell et al (2016) and Cui et al (2017) estimated that CH 4 emissions from dairy livestock in the San Joaquin Valley are up to 2.4 times greater than CARB estimates. Other regional short-term TD measurements have suggested that dairy livestock emissions are similar to CARB estimates (Peischl et al, 2013;Wecht et al, 2014b).…”
Section: Introductionmentioning
confidence: 93%
“…Regional top-down (TD) measurements, which used inverse modeling to attribute CH 4 emissions to different emission sources, have suggested that the national and California inventories underestimate CH 4 emissions from livestock (Miller et al, 2013;Wecht et al, 2014a;Bergamaschi et al, 2015;Jeong et al, 2016;Cui et al, 2017). Based on long-term measurements, Miller et al (2013) estimated that national CH 4 emissions from ruminants and manure management are up to 2 times greater than the US Environmental Protection Agency (EPA) inventory estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres estimate CH 4 emissions in California using aircraft measurements (Cui et al, 2015(Cui et al, , 2017. We assume that concentration deviations above background values and emissions follow lognormal distributions associated with the errors (the model-observation mismatch and flux error) to be of multiplicative nature (Bocquet et al, 2010;Tian et al, 2013).…”
Section: 1029/2018jd029489mentioning
confidence: 99%
“…As CH 4 emanates from numerous reported and unreported sources (Turner et al, 2017), atmospheric studies have played a significant role in evaluating CH 4 emissions (Cui et al, 2017;Ganesan et al, 2017; 10.1029/2019GL082131 Ren et al, 2018;Schwietzke et al, 2016). In comparison to site-level data collected from various anthropogenic sources, atmospheric measurements integrate emissions across large areas, from both natural and man-made sources, allowing for detection and quantification of sources that may be missed or underrepresented in bottom-up inventories (Levin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%